Thyroid status, insulin sensitivity and glucose tolerance in overweight and obese adults before and after 36 weeks of whey protein supplementation and exercise training. (2nd April 2016) - Wright, Christian S.; Craddock, Amy; Weinheimer-Haus, Eileen M.; Lim, Eunjung; Conley, Travis B.; Janle, Elsa M.; Campbell, Wayne W.
ABSTRACT: Research suggests that subclinical hypothyroidism (SHT) influences insulin sensitivity and glucose tolerance. Reductions in thyroid stimulating hormone (TSH) concentrations are associated with exercise training (ExTr), which improves insulin sensitivity and glucose uptake.Purpose: A secondary analysis of previously published data was conducted to examine the relationship between SHT, TSH and glucose homeostatic control at baseline and to assess the impact of ExTr on thyroid status and how SHT affects changes in insulin sensitivity after ExTr.Materials and methods: Data were obtained from a 36-week ExTr and whey protein supplementation intervention trial. Subjects ( n = 304, 48 ± 7 years, females = 186) were randomized to a specific whey protein group (0, 20, 40, or 60 g per day) and all subjects participated in a resistance (2 d/wk) and aerobic (1 d/wk) training program. Testing was conducted at baseline and post-intervention.Results: At baseline, 36% ( n = 110) and 12% ( n = 35) of subjects were classified with SHT based on the TSH ≥ 3 µIU/L or TSH ≥ 4.5 µIU/L cut-offs, respectively. No association was found between baseline TSH and baseline measures of glucose homeostatic control. Whey protein supplementation did not influence intervention outcomes. Post-intervention ( n = 164), no change was observed in TSH. SHT did not affect changes in insulin sensitivity following ExTr.Conclusion: These results support that the health benefits of ExTr for the management of insulin resistance (IR) are not blunted by SHT.